The Relation Between Technology Acceptance and Music Listening: An Experience Sampling Study - Nicolas Ruth; Florian Hantschel; Tim Loepthien; Will M. Randall; Jochen Steffens (Jahrbuch Musikpsychologie, 2024)
In the intersection of technology and music listening, understanding user experiences is paramount. This research employed the Experience Sampling Method via the smartphone app MuPsych to continuously capture real-time data on individuals' music listening behaviors and related emotional responses. Over a span of two weeks, participants from Germany were prompted to report on various factors as they engaged in music listening, resulting in a rich dataset. Results indicate that Spotify Premium was the most frequently used music application, with personal playlists being the preferred listening format. To unravel the intricacies of these responses and their determinants, linear mixed-effects model analysis was utilized. Among the critical findings, the Perceived Usefulness and Perceived Ease of Use, two of the central constructs of the Technology Acceptance Model, emerged as significant predictors for the valence and enjoyment of the music experienced by users during the onset of music listening sessions. This highlights the imperative role of user-friendly interfaces in enhancing positive emotional states even before fully engaging with the music, underscoring the need for designers and developers of music-related apps to prioritise usability and useful functions.